SERUM INFLIXIMAB MEASUREMENT IN INFLAMMATORY BOWEL DISEASE PATIENTS IN REMISSION: A COMPARATIVE ANALYSIS OF TWO DIFFERENT METHODS IN A MULTICENTRIC BRAZILIAN COHORT - Fábio Vieira TEIXEIRA; Ligia Yukie SASSAKI; Rogerio SAAD-HOSSNE; Julio Pinheiro BAIMA; Daniéla Oliveira MAGRO; Claudio Saddy Rodrigues COY; Paulo Gustavo KOTZE (Arquivos de Gastroenterologia)
ABSTRACT BACKGROUND: Infliximab (IFX) therapeutic drug monitoring is an important tool to guide therapeutic decision in inflammatory bowel disease patients. Currently, there are two methods to measure trough levels of IFX, ELISA assays or rapid tests. Despite that the ELISA assay is the most used method in therapeutic drug monitoring, the results take long to be available for clinical use, and it needs to be performed by trained personnel. In contrary, the results of a rapid test take 20 to 30 minutes to be available and can be performed by non-trained lab personnel. OBJECTIVE: The aim of the study was to compare a rapid test (QB-IFX) for quantitative determination of IFX level to one ELISA assay in a cohort of inflammatory bowel disease patients. METHODS: Cross-sectional multicentric study with 49 inflammatory bowel disease patients on maintenance therapy with IFX. Blood samples for IFX serum levels were collected immediately before infusion. IFX serum levels were classified as undetectable, low (<3.0 μg/mL), adequate (3.1-7.0 μg/mL) or high (>7.1 μg/mL). A sensitivity and specificity of each test and a comparison between tests was based on ROC curves. RESULTS: Thirty-four Crohn’s disease patients and 15 ulcerative colitis patients in clinical remission were evaluated. The majority of patients had low or adequate serum levels of IFX. In relation to the serum levels proportions with the two methods, there was no significant difference (P=0.84). The ROC analysis identified a concentration threshold >2.9 μg/mL with the QB-IFX test (area under the ROC, 0.82; P<0.0001, sensitivity, 100%; specificity, 61.9%), and >3.83 μg/mL using the ELISA assay (area under the ROC, 0.96; P<0.0001, sensitivity, 100%; specificity, 92.9%). CONCLUSION: QB-IFX and ELISA assays to measure IFX levels were comparable. Both methods had accurate sensitivity and specificity to detect undetectable, low and adequate levels, but had showed low specificity for supra therapeutic levels of IFX.